A Comparative Study of Lignocaine, Pethidine, Ketamine and Placebo for Prevention of Pain on Propofol Injection - Naaz, Shagufta; Ozair, Erum; Asghar, Adil (Asian Journal of Medical Sciences, 2021)
Background: Pain caused by propofol injection is a common occurrence. Aims and Objectives: The aim of this study was to compare and evaluate the efficacy of three drugs, lignocaine, pethidine and ketamine for prevention of pain during propofol injection. Materials and Methods: This double blind, placebo-controlled, parallel multi-arm study was done after written informed consent and ethics clearance. Hundred patients of ASA I and II, 18-65 years of age, and with body mass index 18-30 kg/m2 were included. Exclusion criteria were significant cardiovascular or hepatic diseases, renal insufficiency, and a history of allergy to the study drugs. Group A (Normal Saline), Group B (Ketamine 25 mg), Group C (Lignocaine 20 mg) and Group D (Pethidine 25 mg) were pre-treated with 2 ml of the study agents before propofol injection. The primary outcome was the incidence of pain with propofol injection and the secondary outcomes were the induction time, pain scores at various time intervals, the incidence of recall of pain after surgery, haemodynamic changes and adverse effects. Results: There were highly significant differences (p<0.001) in the incidences of pain during propofol injection in group A and the other three groups. The difference in incidence of pain was also significant between Group C and other groups. The differences in the pain scores (p<0.001) and recall of pain (p<0.05) between group A and the other three groups were significant. Conclusion: Lidocaine may be considered as a good choice for the purpose of reduction of pain during propofol injection.